1996
DOI: 10.1523/jneurosci.16-08-02691.1996
|View full text |Cite
|
Sign up to set email alerts
|

Complexity affects regional cerebral blood flow change during sequential finger movements

Abstract: Brain regions activated with complex sequential finger movements were localized by measuring regional cerebral blood flow (rCBF) with positron emission tomography. Whereas the total number and frequency of finger movements were kept constant, the complexity of auditory cued sequential finger movements of the right hand varied, with sequence length as the independent variable. In four conditions of differing complexity, the bilateral primary sensorimotor area, left ventral premotor cortex, posterior supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
152
1
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(179 citation statements)
references
References 49 publications
23
152
1
3
Order By: Relevance
“…This is in line with the finding that even when sequences are performed or learned with the right hand, the right PM appears to play a greater role than its left homologue in sequential production (Seitz and Roland, 1992;Jenkins et al, 1994;Sadato et al, 1996). Based on these and present findings, it could be suggested that there is a right premotor dominance not only in sequential production, but also in perceptual sequential processing.…”
Section: Right Hemispheric Lateralizationsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in line with the finding that even when sequences are performed or learned with the right hand, the right PM appears to play a greater role than its left homologue in sequential production (Seitz and Roland, 1992;Jenkins et al, 1994;Sadato et al, 1996). Based on these and present findings, it could be suggested that there is a right premotor dominance not only in sequential production, but also in perceptual sequential processing.…”
Section: Right Hemispheric Lateralizationsupporting
confidence: 92%
“…Most interestingly for us, all involved brain areas, but particularly premotor areas, have been reported also to underlie the planning and production of motor sequences that follow an external sequential target stimulus, as particularly evident from imaging studies using the serial reaction task paradigm (Gordon et al, 1995;Grafton et al, 1995;Hazeltine et al, 1997;Hikosaka et al, 1998Hikosaka et al, , 1996Honda et al, 1998;Sadato et al, 1996;Sakai et al, 1998;Toni et al, 1998). As expected, the present outcome indicates that an attentively observed sequential signal can be a stimulus sufficient to elicit activations within a brain network closely related to that one that participates in sequential motor behavior.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This finding raises and more independent from guidance by the stimulus due the question why the PMC should respond not only to to a learning process. The premotor role in this senpragmatic object properties, but also to dynamic stimulus sorimotor transformation has been indicated by a number features, such as continuously changing patterns in an of imaging studies [11,14,[19][20][21]23,26,42,51,52,67] using abstract figure sequence.…”
Section: Discussionmentioning
confidence: 99%